The formation of professional and pedagogical culture of the future teacher’s approach kompetentnosny (Pedagogy of Higher and Secondary Education, 2012)
Palshkova I. The formation of professional and pedagogical culture of the future teacher’s approach kompetentnosny.In article formation possibilities professionally – pedagogical culture of future teachers of elementary school are opened by means of a kompetentnosny approach. The professional and pedagogical culture is a difficult dynamic process of gradual formation of professional knowledge, professional abilities and professionally meaning qualities of the personality. Kompetentnosny an approach assists professional formation of the identity of future teacher.
Keywords: professional; pedagogical culture; kompetentosny approach